Virtual Touch Tissue Imaging on Acoustic Radiation Force Impulse Elastography: A New Technique for Differential Diagnosis Between Benign and Malignant Thyroid Nodules. (1st April 2014) - Zhang, Yi-Feng; He, Yong; Xu, Hui-Xiong; Xu, Xiao-Hong; Liu, Chang; Guo, Le-Hang; Liu, Lin-Na; Xu, Jun-Mei
Abstract : Objectives: Acoustic radiation force impulse elastography is a newly developed ultrasound elasticity imaging technique that included both Virtual Touch tissue quantification and Virtual Touch tissue imaging (VTI; Siemens Medical Solutions, Mountain View, CA). This study aimed to evaluate the usefulness of VTI in differentiating malignant from benign thyroid nodules. Methods: This study included 192 consecutive patients with thyroid nodules (n = 219) who underwent surgery for compressive symptoms or suspicion of malignancy. Tissue stiffness on VTI elastography was scored from 1 (soft) to 6 (hard). The VTI scores between malignant and benign thyroid nodules were compared. The intraobserver and interobserver agreement for VTI elastography was also assessed. Results: On VTI elastography: score 1 was found in 84 nodules (all benign); score 2 in 37 nodules (3 papillary carcinomas and 34 benign nodules); score 3 in 25 nodules (1 medullary carcinoma, 6 papillary carcinomas, and 18 benign nodules); score 4 in 53 nodules (50 papillary carcinomas and 3 benign nodules); score 5 in 17 nodules (14 papillary carcinomas and 3 benign nodules); and score 6 in 3 nodules (all papillary carcinomas). A VTI elasticity score of 4 or greater was highly predictive of malignancy ( P < .01), and the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 87.0% (67 of 77), 95.8% (136 of 142), 91.8% (67 of 73), 93.1% (136 of 146), and 92.7% (203 of 219), respectively. The κ values were 0.69 for intraobserver agreement and 0.85 for interobserver agreement. Conclusions: Virtual Touch tissue elasticity imaging has great potential as an adjunctive tool combined with conventional sonography for differential diagnosis between benign and malignant thyroid nodules.